PENGARUH LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Milakurnianingsih, Milakurnianingsih (JURNAL MITRA MANAJEMEN, 2025)
This study aims to determine the effect of Leverage as proxied by Debt-to-Equity Ratio (DER), Liquidity as proxied by Current Ratio (CR), and Company Size as proxied (SIZE), on Profitability Return on Assets (ROA) in Registered Pharmaceutical Companies. on the Indonesia Stock Exchange for the 2015-2020 period, either partially or simultaneously. This study determined 7 samples from pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. The method used is Classical Assumption Test Analysis and Linear Regression Test. The results showed that the variables Leverage, Liquidity, and Firm Size had an effect of 69.2% while the remaining 30.8% was explained by other factors outside the research model. With the regression equation Y = -0.020 + 0.590Xâ‚ + 0.075Xâ‚‚ - 0.016Xâ‚ƒ + e. partially leveraged, liquidity has a positive and significant effect on profitability, while firm size has a negative and significant effect on profitability. Simultaneously, leverage, liquidity, and firm size have a positive effect on profitability simultaneously.Â Keywords: Leverage, Liquidity, Firm Size, Profitability